Large Genital Cavernous Hemangioma: A Rare Surgically Correctable Entity - Goto Gangkak; Anoop Mishra; Shivam Priyadarshi; Vinay Tomar (Case Reports in Urology)
We report a case of 24-year-old male presenting with painless penoscrotal swelling for 3 years. On examination, a large soft bag of worm-like, superficial, nonpulsatile swelling was present in scrotum and penis. Color Doppler showed dilated tortuous vessels and on angiography no connections to corpora or vessels were seen. So a diagnosis of hemangioma was made and a surgical excision was carried out by circumcoronal and scrotal incisions. Postop course was uneventful. At 6 months of follow-up, no recurrence was seen and wound had healed with excellent cosmetic appearance.